Avaliação técnica e econômica da implantação de sistemas fotovoltaicos no Aeroporto Internacional de Belém - GONÇALVES, Franciane Andreza Veloso dos Santos (Universidade Federal do Pará, 2015)
This work presents a technical and economic evaluation for the installation of a grid-connected photovoltaic system for the electrification of the International Airport Val-de-Cans, located in Belém - Pará - Brazil. This is a pilot project in the Northern Region of Brazil to be deployed on the roof of the Airport Terminal, in an area of approximately 16.000 m2. The technical evaluation was performed with the aid of meteorological data and that of electrical energy consumption for the period from 2011 to 2012, the design of two options of grid-connected photovoltaic systems (GCPS), the first proposal with 191 subsystems using polycrystalline silicon modules that will generate maximum power of 2.3 MWp in standard conditions, the second proposal with 82 subsystems using amorphous silicon modules that will generate a power maximum of 1.04 MWp in standard conditions. A software is used to simulate the performance of these proposed systems, showing the irradiance and active power profiles for a sunny day and cloudy day. The economic evaluation was based on the designed systems, being decisive for choosing the most suitable photovoltaic system for deployment given that the proposal 1 has an initial investment of R$ 14.970.089,48, reducing the energy consumed in the airport terminal in a maximum of 34% in the month that has the sunniest days, and 24% in the month that has the cloudiest days. This proposal will be payed for itself, in approximately 21 years, without any other contribution sources. Proposal 2 already has an initial investment cost of R$ 10.067.826,13, reducing the energy consumed in the airport terminal in a maximum of 15% in the month that has the sunniest days, and 11% in the month that has the cloudiest days. This proposal won’t be payed for itself, without any other contributing sources. As a result, it is intended to reduce the consumption of energy provided by the electricity utility, to disclose this promising energy alternative and help preserve the environment.